2021
DOI: 10.1088/1361-6455/ac076c
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of trapped-ion qubits to low-dose radiation sources

Abstract: We experimentally study the real-time susceptibility of trapped-ion quantum systems to small doses of ionizing radiation. We expose an ion-trap apparatus to a variety of α, β, and γ sources and measure the resulting changes in trapped-ion qubit lifetimes, coherence times, gate fidelities, and motional heating rates. We found no quantifiable degradation of ion trap performance in the presence of low-dose radiation sources for any of the measurements performed. This finding is encouraging for the long-term prosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this Section, we give a background about quantum computing and the impact of ionizing radiation on qubits, which is essential to understand and appreciate the contribution of our paper. As there is not yet sufficient data on radiation effects on trapped-ion qubits (besides the low-dose test documented in [16]), we will focus the discussion on superconducting materials. Nonetheless, the concepts we introduce, the fault injection framework we design, and the impact of the results we present are independent on the qubit technology, once the fault model is defined.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Section, we give a background about quantum computing and the impact of ionizing radiation on qubits, which is essential to understand and appreciate the contribution of our paper. As there is not yet sufficient data on radiation effects on trapped-ion qubits (besides the low-dose test documented in [16]), we will focus the discussion on superconducting materials. Nonetheless, the concepts we introduce, the fault injection framework we design, and the impact of the results we present are independent on the qubit technology, once the fault model is defined.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In fact, recently pioneer works have demonstrated that, besides noise, it is necessary to harden superconducting qubits also from external radiation [9], [10], [11], [12] as the interaction of ionizing particles significantly reduces the fault tolerance of qubits [13], [14], [15]. Trapped-ion qubits are found to be robust to low-dose low-energy radiation [16], but no data is available for heavier particles, yet. As most studies focus on superconducting qubits we will consider this technology as case study.…”
Section: Introductionmentioning
confidence: 99%
“…on radiation effects on trapped-ion qubits (besides the lowdose test documented in [19]), we will focus the discussion on superconducting materials. Nonetheless, the concepts we introduce, the fault injection framework we design, and the impact of the results we present are independent on the qubit technology, once the fault model is defined.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Recently, pioneer works have demonstrated that it is necessary to harden superconducting qubits also from ex-ternal radiation [9], [10], [11], [12] as the interaction of ionizing particles significantly reduces the fault tolerance of qubits [13], [14], [15]. Trapped-ion qubits are found to be robust to low-dose low-energy radiation [16], but no data is available for heavier particles, yet. Already being one of the challenges for today's classical computing systems, then, ionizing radiation is expected to be a major issue also for future quantum (super) computers [10], [12].…”
Section: Introductionmentioning
confidence: 99%